2017
DOI: 10.19052/mv.5173
|View full text |Cite
|
Sign up to set email alerts
|

Tasa de incidencia de mastitis clínica y susceptibilidad antibiótica de patógenos productores de mastitis en ganado lechero del norte de Antioquia, Colombia

Abstract: ResumenIntroducción: la mastitis se define como la inflamación de la glándula mamaria causante de grandes pérdidas económicas en hatos lecheros, lo que amerita su investigación. Objetivo: determinar la tasa de incidencia de mastitis clínica TIMC, la etiología asociada y la sensibilidad antibiótica de patógenos aislados de casos de mastitis en ganado lechero. Materiales y métodos: se siguieron 37 hatos por 12 meses para el diagnóstico de mastitis cílínica (MC). A las muestras de leche de los casos de MC se les … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
3
2
0
Order By: Relevance
“…Regarding the antibiotic susceptibility profiles obtained, the penicillin and lincomycin showed the highest resistance profile. These results are consistent with those reported by other studies carried out in the same region (Ramírez et al, 2018;Ramírez et al, 2011) and in studies performed in China, as well as in Sweden and Tunisia, which also reported high penicillin resistance (Ben Said et al, 2016;Käppeli et al, 2019;Liu et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the antibiotic susceptibility profiles obtained, the penicillin and lincomycin showed the highest resistance profile. These results are consistent with those reported by other studies carried out in the same region (Ramírez et al, 2018;Ramírez et al, 2011) and in studies performed in China, as well as in Sweden and Tunisia, which also reported high penicillin resistance (Ben Said et al, 2016;Käppeli et al, 2019;Liu et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, studies from the same study area on Klebsiella spp. isolated from dairy cattle with clinical and subclinical mastitis showed a 40% susceptibility to ampicillin [44], whereas in other countries the rate of resistance to the same antibiotic was variable [23,[46][47][48][49]. In addition, the fosfomycin resistance detected in this study is consistent with previous studies reporting K. pneumoniae from raw milk [47].…”
Section: Discussionsupporting
confidence: 89%
“…Regarding to antibiotic susceptibility of isolates evaluated, E. coli isolates obtained were sensitive to all the antibiotics, however, other local studies have shown resistance patterns of E. coli isolated from bulk milk samples [17] and from bovine mammary quarter samples [44] in the same region and in other regions of Colombia [45]. In contrast, studies from the same study area on Klebsiella spp.…”
Section: Discussionmentioning
confidence: 81%
“…According to the phenotypic predictions performed in PATRIC and confirmed by Vitek R 2 system, S. aureus Sa1FB is susceptible to different antibiotics and resistant to penicillin. Previous works performed in the region showed the same behavior (penicillin resistance) in the evaluated S. aureus strains (47,48). Despite low antibiotic resistance found in Sa1FB, a study reported that S. aureus strains carrying the bap gene were less susceptible to antibiotic treatments when forming biofilm in vitro and more persistent in the bovine mammary gland (22).…”
Section: Discussionsupporting
confidence: 55%